Do Massage and Relaxation Music Therapy Increase Breast Milk Volume? A Meta-Analysis - Sakinah, Sakinah; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2023)
Background: Breast milk contains various nutrients that meet the needs of infants’ growth and development. Furthermore, breast milk also contains various antibodies that will protect infants from viruses and bacteria to avoid infections and various diseases. Various conditions encountered by postpartum mothers often lead to stress and anxiety that generate a low milk supply, thus the infants do not get breast milk optimally. This study aims to discover the effect of massage and relaxation music therapy on breast milk volume. Subjects and Method: The study used systematic review and meta-analysis using the PICO model. Population= postpartum mother, Intervention= massage and relaxation music therapy, Comparison= no massage and relaxation music therapy, and Outcome= breast milk volume. Article search was conducted in various databases, namely PubMed, BMC, ScienceDirect, ResearchGate, SpringerLink, and NCBI. The articles were collected in 1 month. The articles were published from 2012-2022. The keywords in this article search were